Family Succession and Responsibilities Towards Female Gender in M’muock Villages, South West Region, Cameroon - Akwanga, Nina (CenRaPS Journal of Social Sciences, 2020)
The article ‘Family succession and responsibilities towards female gender in M’muock villages” is an attempt to examine the role of successors towards the female gender and gender inequality. Using a mixed approach, 300 questionnaires were administered to randomly selected households while in-depth interviews were conducted with some family heads, traditional rulers and notables. Questionnaires were analyzed qualitatively while interviews were exploited using content analysis. Results depicts that family succession in the M’muock villages is discriminatory as the girl child is not allowed to succeed the father. This idea, which is backed by traditional beliefs and customs was supported by about 70% of the population. Women are given out for marriage and are not allowed to have a share of their father’s wealth. However, surveys revealed that women could only take over if there is no male child in the family or when he is incapacitated. This is seen as aspect of gender inequality and discrimination against the female folk. Nevertheless, the degree of responsibility of the child (30%), affectation towards a particular wife (44,4%°), level of education (10%), success in life (10%) and ignorance on the part of the deceased family head were identified as being accountable for changes in successorship. Gender that gender inequality prohibited by the law, this work recommends that parents should empower the girl child and give them equal opportunities as far as inheritance is concerned.